(untitled) (European Science Methodical Journal, 2023)
The article is devoted to the process and the result of the development of the level system of forming communicative competence of future teachers during their University training. The formation of communicative competence of future teachers is an integral part of the system of their professional-pedagogical formation. The development of the level system to determine the degree of communicative competence formation of the students of pedagogical areas will contribute to the improvement of their training as it will allow to develop the criteria of these competencies formation. A multi-level system of formation of communicative competence facilitates the process of student`s entering the professional activity, so as a future teacher and a practicing teacher are in different positions regarding pedagogical activity and pedagogical process. The presented system provides a gradual complication of the student activity on several parameters: the object of activity (interaction with an individual and with a group,); the content of activities (from mastering the elementary skills of pedagogical communication to generalized communicative skills involving proficiency in methods and techniques of pedagogical activities); the nature of activities (reproductive or creative). Basing on our own theoretical and practical research, we present a table, organizing the levels and criteria of formation of communicative skills on the stages of solving different kinds of problems: analytical, constructive and practical. It was created on the analysis of the structure, content and the amount of communicative skills necessary for increasing the efficiency of pedagogical activity.